Efficacy of autologous platelet rich fibrin matrix in the management of non-healing ulcers - Gole, Prachi V.; Muhammed, Naziya; Patadia, Siddhi R. (International Journal of Research in Dermatology, 2019)
Background: Non healing ulcers have a worldwide prevalence of 1.9%-13.1% with lower extremity being the commonest site. They are difficult to manage for the physician and frustrating for the patient due longer duration of treatment, cost, unsatisfactory outcomes and impairment caused due to them. Standard conventional management may fail at times and hence growth factors derived from platelets have been tried in the management of these ulcers. The purpose of our study was to evaluate the efficacy of platelet rich fibrin matrix (PRFM) in treatment of these ulcers. Methods: Twelve patients with fifteen non-healing ulcers more than 3 months duration were included in the study. 10cc of venous blood was withdrawn in plain tube without anti-coagulants and centrifuged at 1500 rpm for 14 minutes as early as possible as per advanced PRF protocol. Middle layer of PRFM was applied to the clean ulcer followed by a secondary dressing. All patients received PRFM sittings every 7-10 days or till ulcer healed. Baseline photographs and measurements of length, breadth and depth were taken to calculate the area of ulcer at every sitting. Results: The average percentage reduction in area and volume of the ulcer was 95.84% and 98.18% respectively at the end of six sittings. Twelve out of fifteen ulcers showed complete healing by 6 weeks, while three ulcers showed significant improvement but did not heal completely. The procedure was safe, well tolerated without any side effects. Conclusions: Platelet rich fibrin matrix is a novel modality and an ideal, safe, affordable therapeutic option for non-healing wounds of varied causes.